PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU PENYAMPAIAN PELAPORAN KEUANGAN - Rahmatia, Utami; Hendra Ts, Kartika; Nurlaela, Siti (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
The purpose of this study is to discuss and analyze the influence of independent commissioners, public accounting firms, the opinions of auditors and audit institutions on the timeliness of financial reporting. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) 2016-2018 period. The sampling technique in this study used a purposive sampling method while the samples used in the study were 13 companies. The data used are secondary data obtained from the Indonesia Stock Exchange, the data is processed using SPSS 22. The results showed that the independent commissioner variable did not have a significant effect on the timeliness of financial reporting. The reputation of the public accounting firm has a significant influence on the timeliness of financial reporting. Audit opinion has a significant influence on the timeliness of financial reporting. The Audit Committee has no significant effect on the timeliness of financial reporting. Whereas together with the independent commissioners, the reputation of the Public Accounting Firm, the audit opinion and the audit committee have an influence on the delivery of financial reporting time